Narrating the real corporate story - Ambler, Tim; Neely, Andrew (Blackwell Publishing Ltd, 2008)
Companies are being pressed to be more transparent in their annual reporting and, at the same time,interest is moving from the formal accounts to the narrative sections, partly in response to the increasing importance of the intangible assets not on the balance sheet. The paper sets out the changes in UK requirements, ummarised in a Framework provided by the Worshipful Company of Marketors, and company practice. The two weakest areas in relation to the Accounting Standards Board Reporting Standard are the provision of forward looking information and non-financial KPIs, especially those to do with customers, competitors and brands. The paper suggests that brand equity, the intangible marketing asset, is the present reservoir of future cash flow. Accordingly, provision of professional measures of brand equity should go some way towards solving both weaknesses at the same time.